Timely, Transcendent, and Alive: Trinity in Jenson's Understanding of the God–World Relation. Issue 3 (August 2019) - Rice, Scott P.
Robert W. Jenson conceives of the God-world relation through a temporally inclusive idea of God that many critics find objectionable. Central to Jenson's proposal is that God precedes the history that God lives with others by means of God's own future. Does this make sense? In this essay I argue that it does, and that Jenson's account needs to be demystified. The key to this, particularly, demonstrating the coherence of the God-time relation in view of the divine futurity, lies in the understanding of Jenson's trinitarian theology. I will show that Jenson's temporal idea of God, with a focus on his doctrine of the Spirit, is consonant with the trinitarian relations and should not be identified with the poles of created time in an overtly literal way. I also draw on Jenson's trinitarian logic of divine unity to illustrate the reality of God in the process of time in his doctrine of creation.